2018
DOI: 10.1186/s13033-018-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Family assessment conversations as a tool to support families affected by parental mental illness: a retrospective review of electronic patient journals

Abstract: BackgroundPrevious research has shown a link between parental mental illness and adverse development in their offspring. In Norway, it is mandatory for health professionals to identify if patients in adult mental health services have children, and subsequently to provide support for the children. An important tool to detect if families are affected by parental mental illness and to assess if there is a need for further intervention is the Family Assessment Conversation. Family Assessment Conversations is poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Det er derfor et nedslående funn at informantene opplevde lite hjelp og støtte fra helsepersonell til tross for deres lovpålagte plikt om informasjon og oppfølging av barn som pårørende. Samtidig understøtter disse funnene tilsvarende resultatene fra flere norske studier (Lauritzen et al, 2018;Ruud et al, 2015). Dette kan bety at foreldre i stor grad står alene i en svaert utfordrende situasjon, og synliggjør en manglende implementering av gjeldende lovverk (Helsepersonelloven, 2010, §10a).…”
Section: Diskusjonunclassified
“…Det er derfor et nedslående funn at informantene opplevde lite hjelp og støtte fra helsepersonell til tross for deres lovpålagte plikt om informasjon og oppfølging av barn som pårørende. Samtidig understøtter disse funnene tilsvarende resultatene fra flere norske studier (Lauritzen et al, 2018;Ruud et al, 2015). Dette kan bety at foreldre i stor grad står alene i en svaert utfordrende situasjon, og synliggjør en manglende implementering av gjeldende lovverk (Helsepersonelloven, 2010, §10a).…”
Section: Diskusjonunclassified
“…One study showed that 56% of health personnel at a large Norwegian university hospital did not identify patients' children (39), and a 5-years follow-up study showed that 28% of the health personnel in the same clinic still did not identify patients' minor children (42). Another recent Norwegian study showed that only 17% of patients in two psychiatric hospitals were assessed completely with family assessment forms (43). These results indicate that although the law requires identification of COPMI and provision of support in Norway, there has not been sufficient systematic work around implementing new clinical practice related to this issue in adult mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…Family assessment is a part of the evaluation but also can be used anytime to understand changes within each family. It also focus on the resources the family uses to support child development [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%